Energy storage applications of graphene-based materials - Lai, Linfei (2013)
This thesis focuses on the investigation of chemically prepared graphene/ graphene composites and their application as new energy storage materials. The surface chemistry of graphene was found to be important for the growth of conducting polymer and further influences the magnitude of increase of specific capacitance. Nitrogen-doped graphene (N-graphene) and non-precious metal nitride catalyst (FeCo-N complex) are successfully prepared and demonstrate its use as a noble metal-free catalyst to study the catalytic active center for the oxygen reduction reaction (ORR). The bonding state of the N atoms was found to have a significant effect on the selectivity and catalytic activity for ORR. The ORR mechanism and the nature of the active centers of graphene based non-precious metal catalyst were rationalized based on UPS, XPS, XRD, and linear sweep voltammetry data. The data suggest that non-precious metal catalysts can be effective for ORR.